Manajemen Pemasaran Dalam Meningkatkan Mutu Pendidikan di SMA Negeri 1 Torjun - Munib Munib; Tajul Anwar; Abdullah Sarif; Fathorrahman Z (AL -ALLAM, 2023)
In the current era of globalization, competition between educational institutions is currently increasingly attractive and competitive, therefore it is necessary to have good marketing activities in order to build a positive image and attract public interest. In marketing, the things that must be considered by the students themselves are because the students are the products that will be offered. That way education must be able to produce good or quality products so that it can attract public interest. Based on this, there are three problems that are the main study in this study, namely: first, how to plan marketing management in improving the quality of education in SMA Negeri 1 Torjun, second, how to implement marketing in improving the quality of education in SMA Negeri 1 Torjun, third, how evaluation of marketing management in improving the quality of education at SMA Negeri 1 Torjun. This research uses a qualitative approach that is descriptive. The data sources obtained are through interviews, observation and documentation. The informants were the principal of Torjun 1 Public High School, deputy head of curriculum and Torjun 1 Public High School students. efficient.